Myllocerus discolor - a pest of ber (Ziziphus jujube) in Tripura, India - Das, Jhuma; Das, Ashok (Asian Journal of Biological and Life Sciences, 2016)
in the state of Tripura, northeast India. It is a severe pest of Ziziphus jujube which is an economically important crop in Tripura.
Keywords: Ziziphus jujube; Myllocerus discolor; Tripura; pest